Pendidikan Karakter Melalui Kuntau Seni Beladiri Masyarakat Banjar Di Kalimantan Selatan - Rabi'ah, Rabi'ah (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2019)
Character education is one of the national education programs that is always promoted for the younger generation, ranging from Basic Education to Higher Education. The government thinks character education is a solution to various problems, ranging from corruption, intolerance, to environmental problems such as garbage and floods. Various methods are used in order to grow these characters. The focus of this research is how character education is in accordance with the values of Islamic teachings through the Kuntao martial arts. Kuntao is a traditional martial art that has long been practiced by the Banjar people in South Kalimantan. This research is expected to provide a new treasure about the contribution of the traditional martial arts of the banjar community in Islamic education. The research method used is a qualitative method with an ethnographic approach. The subjects of the study were the martial arts teacher, students, peers, and parents. Data analysis using miles and Huberman analysis. Data validity through source triangulation. The results of this study are that character education through martial arts has fulfilled the 3 pillars of character education in Islamic education namely morals, etiquette, and exemplary. Being obedient in carrying out the Islamic Shari'ah, respecting others, self-confidence, and humility are the characters that are formed through the teaching of martial arts in the Banjar community. In harmony with Islamic values that can not be separated from the role model of the teacherâ€™s kuntao.Â Â